(3GdaJM GdWQj GdLfi aj HYV eBKQ TjNfG GdTjN YHOGdZfj (B((3GdfGHdSj(B)s - (3eUWaj Hf ceGd GdOjf Hf Ydj GdHcQj GdUOjbj, GdNdhJj, GdMfaj , CHh GdehGgH,J (B1162 (3g` s ((3MSjf Hf CMeO GdcHjSj s)
(3ChdgG (B:s
(3CeG HYO deG HdZfi NHQ haGI TjNfG GdTjN YHOGdZfi SGAfj eG SeYJ CPfihcfJ CQSdJ dg ecGJHGJ aCMHHJ Cf CPcQgG ai gPG GdcQGS NhakG YdjgG ef GdVjGY s
(3BNQgG (B:s
(3hCf jfYe YdjfG HMSf GdNJGe HLGg NGJe GdCfHjGA hGdCYdGe , hjefMfG hGaQ GdEcQGe aj efGRd EcQGeg hGdMeO ddg QH GdYGdejf s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B239 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B271 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B5 - (3U (B449s
(3Sdc GdOQQ (B- (3GdLRA (B4 - (3U (B197 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B304 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs